3x+5+12x+7x=-14x-12+1

Simple and best practice solution for 3x+5+12x+7x=-14x-12+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5+12x+7x=-14x-12+1 equation:


Simplifying
3x + 5 + 12x + 7x = -14x + -12 + 1

Reorder the terms:
5 + 3x + 12x + 7x = -14x + -12 + 1

Combine like terms: 3x + 12x = 15x
5 + 15x + 7x = -14x + -12 + 1

Combine like terms: 15x + 7x = 22x
5 + 22x = -14x + -12 + 1

Reorder the terms:
5 + 22x = -12 + 1 + -14x

Combine like terms: -12 + 1 = -11
5 + 22x = -11 + -14x

Solving
5 + 22x = -11 + -14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14x' to each side of the equation.
5 + 22x + 14x = -11 + -14x + 14x

Combine like terms: 22x + 14x = 36x
5 + 36x = -11 + -14x + 14x

Combine like terms: -14x + 14x = 0
5 + 36x = -11 + 0
5 + 36x = -11

Add '-5' to each side of the equation.
5 + -5 + 36x = -11 + -5

Combine like terms: 5 + -5 = 0
0 + 36x = -11 + -5
36x = -11 + -5

Combine like terms: -11 + -5 = -16
36x = -16

Divide each side by '36'.
x = -0.4444444444

Simplifying
x = -0.4444444444

See similar equations:

| 0=x^2-5x+6 | | 12y-5=24y+4-13 | | -12w-4+3w-7=4 | | 3(5y-3)=6y | | 3x-4x-4=0 | | 4y+14=3 | | 6y-3(y-3)+6= | | 5p-22=-30+4p | | 3x-29=-23+9x | | 6.75+b=7.5 | | 66.8*2x=30 | | B=yx+m | | -x^2-3x-8=0 | | w/10=6 | | -1/6-7-7 | | 125x^3-216r^3= | | d-9=-16 | | 5/9(77-32) | | -x/-6=10 | | -(1/5)x-4 | | 8x^3-24x^2-1664x= | | 1/3*(2x-5)=3 | | 7s^2+19s+10= | | y=3x^2-30x+71 | | 2x+2x+5=17 | | 315=5x^3 | | 8p^2-21p-36=0 | | C=200+.75Y | | (4v-3p)(4v+2p)= | | 5x-1=3x+2-x^2 | | 4y^2+4y=80 | | 100.00+8.00=10.00x |

Equations solver categories